ChemInform Abstract: Direct Conversion of N‐Alkoxyamides to Carboxylic Esters Through Tandem NBS‐Mediated Oxidative Homocoupling and Thermal Denitrogenation. Issue 5 (4th February 2014) - Zhang, Ningning; Yang, Rui; Zhang‐Negrerie, Daisy; Du, Yunfei; Zhao, Kang
Abstract This method is suitable for the synthesis of sterically hindered carboxylic esters.